2007
DOI: 10.1080/17450390701431540
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the probiotic bacteriaEnterococcus faeciumNCIMB 10415 (SF68) andBacillus cereusvar. toyoi NCIMB 40112 on the development of serum IgG and faecal IgA of sows and their piglets

Abstract: To examine the influence of two different probiotic bacteria on the humoral immune system of swine, two animal studies were carried out with sows and their litters. The sows' feed was supplemented with either Enterococcusfaecium NCIMB 10415 (SF68) or Bacillus cereus var. toyoi NCIMB 40112 beginning early in pregnancy. The total IgA content in the faeces as well as the total IgG concentration in the blood of the sows was recorded before and after weaning. The same parameters were determined in the blood and fae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 22 publications
2
38
0
Order By: Relevance
“…faecium NCIMB 10415 reduced the number of intraepithelial cytotoxic T-cells and fecal IgA in weaned piglets (Scharek et al 2005;Scharek et al 2007). Further analyses confirmed that E.…”
Section: Prevention Of Diarrheamentioning
confidence: 99%
See 2 more Smart Citations
“…faecium NCIMB 10415 reduced the number of intraepithelial cytotoxic T-cells and fecal IgA in weaned piglets (Scharek et al 2005;Scharek et al 2007). Further analyses confirmed that E.…”
Section: Prevention Of Diarrheamentioning
confidence: 99%
“…toyoi NCIMB 40112, and suggested that the probiotic effect may be attributable to increased IgA providing better protection at mucosal surfaces (Scharek et al 2007). …”
Section: Ruminococcus-enterotype By Treponema (Ramayo-caldas Et Al 2mentioning
confidence: 99%
See 1 more Smart Citation
“…In a study, in which pregnant sows were given either B. cereus or E. faecium significant decreases were seen in the serum IgG levels of the piglets post-weaning, perhaps reflecting the increased stability of the gut wall, with a concomitant reduction in translocation of bacteria from the gut into the systemic circulation (Scharek et al, 2007).…”
Section: Probiotic Actions On Host Physiologymentioning
confidence: 99%
“…Treatment of sows and their litters with feed supplemented with B. cereus var Toyoi reduced carriage of pathogenic E. coli strains and resulted in altered absolute numbers and distributions of immune cells in the piglets (Scharek et al, 2007). Piglets from the group given the microbial supplement had a reduced incidence of diarrhoea and liquid faeces; they also had higher average daily gains and feed : gain ratios (Taras et al, 2005).…”
Section: Direct Fed Microbialsmentioning
confidence: 99%